Orbital lymphangioma: a surgical challenge - Ramalho, M (2013)
Lymphangioma is an uncommon venolymphatic lesion with dead-end lymphatic channels, also defined as vascular hamartoma of lymphatic origin. Orbital lymphangiomas present management challenges to the ophthalmologist due to the tendency to recur locally unless it is completely excised, this is often difficult, because lymphangiomas tend to be infiltrative. The recurrence of hemorrhage and expansion can lead to vision loss and disfigurement. Case report: A 22-year-old woman who had a right orbital lesion excised when she was 18 months, with the confirmation of the clinical suspicion of lymphangioma, had also undergone surgery for another 3 times with a different surgeon. The patient presented with conjunctival chemosis, proptosis, exotropia, and no vision in the right eye, this symptoms had been present for several years. On ophthalmic examination, visual acuity was light perception in the right eye and 10/10 in the left eye. The biomicroscopy of the right eye revealed a punctate keratitis and an exuberant chemosis. The patient had proptosis and a limitation on the adduction of the right eye. Extensive orbital excision of the lymphangioma was performed with symptomatic improvement. After 13 years of follow-up the symptoms recurred progressively associated with recurrent corneal ulcers and pain, an evisceration was performed. The patient presented with adherences and fibrosis in the anophtalmic socket with the need for 2 surgerys for the excision of adherences and 1 surgery for correction of ectropion. Functional as well as aesthetic outcome was obtained. Conclusion: Orbital lymphangiomas represent unique treatment challenges. These infiltrative lesions are prone to recurrence with bleeding, disfigurement, vision loss, and diplopia and can result in disfigurement. Complete surgical excision, as in this case, is typically unattainable without